Etienne de Villiers as etikus van verantwoordelikheid - Dirkie Smit (Verbum et Ecclesia, 2012)
Etienne de Villiers as ethicist of responsibility. The paper considered six ways to describe Etienne de Villiers as ethicist of responsibility. They broadly corresponded with chronological phases in his academic career. The first was the way in which he initially took responsibility to teach theological ethics in a methodologically reflective way. The second was the way in which he increasingly found answers to these methodological concerns in responsibility ethics as an approach. The third was the way in which he spent much time analysing the work of responsibility ethicists. This critical engagement led to a fourth phase, still ongoing, developing his own approach. Against this background, the paper argued that he had always been an ethicist of responsibility in the fifth sense that he addressed urgent moral challenges. Developing this, a final section claims that he was an ethicist of responsibility according to Webers description of science as vocation. The paper was read as key note presentation at the University of Pretoria on 09 November 2011, when D.E. (Etienne) de Villiers was honoured on the occasion of his retirement. On the specific request of the organisers, the speech was held in Afrikaans and the original oral form was retained here, including the personal rethorical style of the introduction and conclusion.